Repositioning Interest Sharing and Profit Sharing in Islamic Finance Implications of Big Data in the Era of Disruption - Nabila Novita , Akne; Fauzi, Ahmad; Wildan Sholihi , Ahbib (ASAS, 2025)
This study examines Islamic economic law in the era of digital disruption, focusing on issues of interest, profit-sharing systems, and the use of big data in Islamic finance. The key question is how Islamic economic law can remain relevant to technological developments while upholding justice, transparency, and compliance with maqasid al-sharia. Using the library research method with a normative-juridical approach, this study reviews the Qur'an, hadith, fiqh literature, national regulations, and fatwas. The findings suggest that revenue sharing offers a fairer mechanism compared to interest, while big data can improve transparency and efficiency if managed ethically. The study concludes that digitalization can increase the legitimacy of Islamic finance, as long as it is supported by proper data governance and in line with Islamic values.